Briefing: Why knowledge-based construction is needed for a 1·5°C world. Issue 1 (March 2017) - Clarke, Keith
Abstract : Most countries in the world have agreed to limit the average global temperature change to 2°C, with an aspiration to keep it to 1·5°C. Constructing the built environment for the additional three-to-four billion people on the planet, accommodating the roughly three billion who will expect to join the 'middle class' and meeting the United Nations' development goals are all fantastic challenges and arguably could be met by the existing industry by trying harder. Add reducing the carbon dioxide emissions of the global economy very, very quickly as a conditioner on all of the above, and a different industry is both required and likely to emerge.